The addition of egg yolk to the physiological saline extender improved the motility and viability of kampung rooster spermatozoa at cool temperatures - Diba, Lucky; Suzanita Utama; Tjuk Imam Restiadi; Suherni Susilowati; Nusdianto Triakoso; Dwi Wijayanti (Universitas Airlangga, 2023)
The purpose of this study was to determine the motility and viability of kampung rooster (Gallus gallus domesticus) spermatozoa in 0.9% Sodium chloride (NaCl) solution as an extender with the addition of egg yolk at different concentrations at cool temperature (5°C). This study was performed using two 1.5 years old healthy local roosters. Semen was collected through massage in the morning. The pooled semen sample was divided into four treatment groups. In the T0 group the semen was diluted in 0.9% NaCl, while in the T1, T2 and T3 groups the semen was diluted in 0.9% NaCl added with 5, 10 and 15% egg yolk. The results showed that the motility and viability of spermatozoa decreased when stored at cool temperatures for ten hours (p <0.05). Semen of roosters stored at 5°C in saline solution without the addition of egg yolks showed the lowest motility and viability of spermatozoa (p <0.05). The addition of egg yolk into the saline extender increased the motility and viability of spermatozoa. Concentration of 15% egg yolk in saline solution resulted in the highest spermatozoa motility and viability when stored for up to 8 hours (p <0.05). However, motility and viability of spermatozoa at 10 hours of storage were not significantly different (p >0.05) with the addition of 10% and 15% egg yolks. Therefore, it could be concluded that the addition of 15% egg yolk into a saline solution as an extender could maintain the motility and viability of kampung rooster spermatozoa when stored at 5°C for 10 hours.